Insect Pest Associated With Tomato In Local Vegetable Markets Of Sindh, Pakistan - Khoso, Abdul Ghaffar; Ahmed, Saeed; Asghar, Farrukh; Khan, Mansab; Aziz, Enayat; Asghar, Khalil (International Journal of Applied Sciences and Biotechnology, 2019)
Study was carried out on “Insect pests associated with tomato in local vegetable markets of Sindh, Pakistan” during November and December 2018. The insect pests’ infested-tomatoes are also sold in local vegetable markets and consume by people in Sindh, Pakistan. In present study was seen that the tomato fruit borer (caterpillar) fed symptoms, it had holed and bored, starting where the stem is attached to the fruit and these were ripped tomatoes and red colour. Insect infested tomatoes were collected; the thickness, length, the holes and inner fruit (interior) portions of the fruit damaged by the larvae were also measured and examined. A random selection of 30 vegetable vendor shops was selected in each city of Sindh. The largest pest infested tomato fruit was 30,120, the minimum was 2, 2 from the stock of 5, 5 kg, and 4, 7 green vegetable vendor shops there no pests found in tomato fruits. Overall, 243,995 insect-infested tomatoes were found in 305,515 kg, 30, 30 vegetable vender shops in Qasimabad and Shahdadkot. The maximum and minimum mean thicknesses and lengths of tomato fruits recorded from Qasimabad and Shahdadkot were 3.73, 3.31 cm, 3.06, 2.82 cm and 5.19, 4.75 cm, and 2.98, 3.7, respectively. The overall maximum and minimum thickness and tomato fruit length were 2.77, 3.83 cm and 2.47, 3.51 cm, respectively. The maximum and minimum mean ​​of tomato fruit hole and depth (internal feeding part) infested by insects were 0.73, 0.94 cm2 and 0.43, 0.61 cm2 and 1.07, 1.01 cm2 and 0.4, 0.38 cm2, respectively. While, the Overall total average hole diameter depth of the insect-infested tomato fruit was 0.51, 1.12 cm2 and the total depth was 0.75, 0.55 cm2 of the Qasimabad and Shahdadkot recorded respectively. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 217-221